PENGARUH KETERAMPILAN PENGUATAN GURU PENDIDIKAN AGAMA KRISTEN TERHADAP TINGKAH LAKU SISWA KELAS XI SMA NEGERI 1 TARUTUNG KABUPATEN TAPANULI UTARA TAHUN PEMBELAJARAN 2019/2020 - Situmeang, Monika (IAKN Tarutung, 2020)
The purpose of this research was to determine the magnitude of PAK teacher strengthening skills effect on XI grade students behaviour of SMAN 1 Tarutung, Taput, academic year 2019/2020The method of this research was inferential quantitative. The population is all christian students on XI grade of SMAN 1 Tarutung which amount to 260 students. The sample was taken 20 % from 260 students = 52 students. The instument of this research was closed questionnaire. Analysis results was r count = 0,534 r table = 0,297 and t count = 4,037 t table = 2,021, showed that there was an effect between strengthening skills of PAK teacher to XI grade students behaviour of SMAN 1 Tarutung, Taput, academic year 2019/2020. Hypothesis test is obtained f count = 37,158 f table = 2,08, that Ho rejected and Ha be accepted.Based on the research result that 71,5 % influenced by other factors as explained in the theory discussion. It was concluded that there is a positive and significant effect between PAK teacher strengthening akilss to XI grade students behaviour of SMAN 1 Tarutung, Taput, academic year 2019/2020.Therefore, the writer gives advice for PAK teacher to increased strengthening skills so it can improve students behaviour better.Keywords: PAK Teacher Strengthening Skills, Student Behavior